FAKTOR-FAKTOR PENENTU KEBERHASILAN BADAN USAHA MILIK DESA DALAM PERSPEKTIF EKONOMI LOKAL - Rosidah, Dewi; Judijanto, Loso; R Pugu, Melyana; Al-Amin, Al-Amin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
Village-Owned Enterprises, often abbreviated as BUMDes, are a manifestation of a business owned and operated by a village. It was established to encourage the village economy. The main problem that is often encountered is that BUMDes are difficult to develop and do not have a real impact on the local village community. The purpose of this study is to provide detailed insights into the significant factors in supporting the success of BUMDes. This research was carried out with a literature study model whose data was taken from scientific articles contained in the google schoolar database starting from 2023-2024. Data analysis was carried out using the Miles and Huberman technique. From the results of the study, it is concluded that BUMDes will be successful if they adopt strategies such as human resource training, technology utilization, and product innovation. Diversification and partnerships can improve performance. Effective marketing management and accurate finances are vital. Full support from the village government is urgently needed.